A construção do poético no roteiro cinematográfico - potência e simbiose - Johann, Ana (2015)
Along its trajectory, the cinema has searched for its particularities, adjusting and changing principles of dramaturgy and literature to the point of building its own parameters. Currently, there is not a big amount of bibliographic production in the screenplay script area. In general, cinema studies focus on films which are already concluded and the contents of script books have a tendency to teach the rules of drama in the conception of the scene. However, there are scripts that do not support only in such writing mechanisms. Therefore, this research has the goal to analyze the scene conception regarding the construction of the poetic from the writing of the script. In order to explore this thematic, we follow the birth of the cinema and the obstacles it faced. On a second look, we analyze some of the main authors that focus on the teaching of script and the scene in contemporaneity: Syd Field, Robert Mckee, Doc Comparato, David Mamet, Lucrecia Martel, Karim Aïnouz, Guilhermo Arriaga, Newton Cannito and Leandro Saraiva. Their lessons have healped to enter the conception of the scene in the movie Django (Quentin Tarantino, 2012,), built and supported in dramaturgical strategies. To the poetic in the scene conception of the screenplay script, we prioritize as the main movie, Amor (Michael Haneke, 2012), among other secondary ones also mentioned. As a theoretical support, we are mainly based on the concepts of fratura e escapatória from the book Da Imperfeição (Algirdas Greimas, 2002); on Poética do Espaço (Gaston Bachelard, 2000) and Transparência e Opacidade (Ismail Xavier, 2005). On this trajectory, some other authors were analyzed such as Christian Metz, Etienne Samain and Erika Savernini.